A Novel Korean Red Ginseng Compound Gintonin Inhibited Inflammation by MAPK and NF-κB Pathways and Recovered the Levels of mir-34a and mir-93 in RAW 264.7 Cells. (12th October 2015) - Saba, Evelyn; Jeon, Bo Ra; Jeong, Da-Hye; Lee, Kija; Goo, Youn-Kyoung; Kwak, Dongmi; Kim, Suk; Roh, Seong-Soo; Kim, Sung Dae; Nah, Seung-Yeol; Rhee, Man Hee
Abstract : The beneficial health promoting effects of ginseng from vitalizing the body to enhancing long life have been well explored very rapidly in the past few years. Up till now many ginsenosides have been discovered for their marvelous therapeutic effects. However during past three years, a novel ginseng compound has been discovered, called gintonin, that differs from other ginsenosides on the basis of its signal transduction and chemical nature. Gintonin has been widely studied for its anti-Alzheimer's disease activities and other neuropathies. However, its anti-inflammatory activity remained unexplored. In our study we have reported for the first time the anti-inflammatory activity of gintonin on RAW 264.7 cells. We found that gintonin potently suppresses the nitric oxide production without any cytotoxicity at given doses and also efficiently suppressed the levels of proinflammatory cytokines. Moreover, it mediaes its signal transduction via MAPK and NF- κ B pathways and revives the levels of mir-34a and mir-93. These findings are valuable for the anti-inflammatory effects of this new compound with particular reference to microRNA involvement in the ginseng family.